2008
DOI: 10.1038/nsmb.1521
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of Pirh2-mediated p53 ubiquitylation

Abstract: Pirh2 (p53-induced RING-H2 domain protein, also known as Rchy1), is an E3 ubiquitin ligase involved in a negative-feedback loop with p53. Using NMR spectroscopy we show that Pirh2 is a unique cysteine-rich protein comprising three modular domains. The protein binds nine zinc ions using a variety of zinc coordination schemes including a RING domain and a novel left-handed β-spiral in which three zinc ions align three consecutive small β-sheets in an interleaved fashion. We demonstrate that Pirh2-p53 interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 36 publications
3
104
0
Order By: Relevance
“…7C shows the results of these experiments, demonstrating that the endogenous p53 from the wild-type p53-expressing HCT116 cells interacts with recombinant GST-Pirh2A and the Pirh2B isoforms but not with Pirh2C. While this manuscript was in revision, a structural study by Sheng et al (35) found that Pirh2 associated with p53 via contacts with the Pirh2 N and C termini. Using various synthetic deletions, one of which corresponded to the region deleted in Pirh2C, the authors concluded that primary binding is dependent upon a C-terminal region of full-length Pirh2 and that the Pirh2 N terminus harbors only weak p53 binding potential (35).…”
Section: Pirh2b and Pirh2c Expression In Various Cellmentioning
confidence: 97%
See 3 more Smart Citations
“…7C shows the results of these experiments, demonstrating that the endogenous p53 from the wild-type p53-expressing HCT116 cells interacts with recombinant GST-Pirh2A and the Pirh2B isoforms but not with Pirh2C. While this manuscript was in revision, a structural study by Sheng et al (35) found that Pirh2 associated with p53 via contacts with the Pirh2 N and C termini. Using various synthetic deletions, one of which corresponded to the region deleted in Pirh2C, the authors concluded that primary binding is dependent upon a C-terminal region of full-length Pirh2 and that the Pirh2 N terminus harbors only weak p53 binding potential (35).…”
Section: Pirh2b and Pirh2c Expression In Various Cellmentioning
confidence: 97%
“…Given that the two proteins bind disparate regions of p53 (11,35), this outcome could be the result of paralleled ubiquitination of p53, and this could be true for Pirh2A that harbors intrinsic E3 ligase activity. However, our results indicate that both Pirh2B and Pirh2C lack ubiquitin ligase activity and Pirh2C has a diminished ability to bind p53.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Studies of the interaction between Pirh2 and p53 showed that Pirh2 preferentially interacts with and leads to the degradation of p53 in its active tetrameric form rather than its monomeric form. 12 Despite the data showing Pirh2 ubiquitylation of p53 and other key cellular proteins, the in vivo functions of this E3 ligase remained elusive. Recently, we reported that in contrast to Mdm2 knockouts, Pirh2 −/− mice were viable and displayed normal development.…”
Section: Pirh2 and P53mentioning
confidence: 99%